2016
DOI: 10.5005/jp-journals-10024-1939
|View full text |Cite
|
Sign up to set email alerts
|

Status of Endodontic Treatment and the Correlations to the Quality of Root Canal Filling and Coronal Restoration

Abstract: The quality of the root filling and coronal restoration is closely related to periapical health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
(54 reference statements)
0
8
0
10
Order By: Relevance
“…However, an incomplete filling can jeopardize the success of root canal treatment. Inadequate endodontic filling is linked to the development Materials 2021, 14, 4013 2 of 15 of periapical pathology and considered a failure of the endodontic treatment [2][3][4]. In a systematic review, Ng et al, found four factors that significantly improve the outcome of primary root canal treatment, and one of these was the presence of a root filling with no voids [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, an incomplete filling can jeopardize the success of root canal treatment. Inadequate endodontic filling is linked to the development Materials 2021, 14, 4013 2 of 15 of periapical pathology and considered a failure of the endodontic treatment [2][3][4]. In a systematic review, Ng et al, found four factors that significantly improve the outcome of primary root canal treatment, and one of these was the presence of a root filling with no voids [5].…”
Section: Introductionmentioning
confidence: 99%
“…24 Moreover, the debate continues among dental practitioners about the selection of the final restoration type once RCT is completed. [25][26][27][28] Pirani et al analyzed a 10-year data in an endodontics master's program and found an 85% success rate of root canal treatment obturated with thermafill and AH Plus sealer. 29 Prati et al found 80% survival of ETT in their 20 years recall study with non-endodontic reasons as the main causes of the extraction of root-filled teeth.…”
Section: Introductionmentioning
confidence: 99%
“… 27 ER outcomes depend on numerous factors, including patient age; treated tooth type; interindividual anatomical variation in the same teeth, the seal of the coronal restoration, the method used to access the existing filling in RC, and the possibility of repairing defects (iatrogenic or pathologic). 28 , 29 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%